Relationship between growth, structure and superconductivity of single crystal YBa2Cu3O7-delta - Chen, C; Wondre, F; Hodby, J; Ryan, J; Narlikar, A; Samanta, S (1999)
We study the crystal growth of YBa2Cu3O7-delta with additives, using ac susceptibility, X-ray diffraction and STM. One specific additive, BaF2, dramatically improves both the crystal growth and the superconducting properties. A cluster growth model is proposed to describe the function of the additive. F- reduces the Al contamination of Cu-O chains, and the orthorhombicity increases. On a nanometer scale, the roughness of the chains decreases markedly. Superconductivity is further enhanced using noncontaminating crucibles. Large single crystals with T-C = 93.7 K and Delta T-C = 0.1 K were grown in Y2O3 or BaZrO3 crucibles using the BaF2 additive.